Blood conservation strategies reduce the need for transfusions in ascending and aortic arch surgery. (July 2013) - Chu, MWA; Losenno, KL; Moore, K; Berta, D; Hewitt, J; Ralley, F
Introduction: Ascending and aortic arch surgery is associated with higher levels of blood loss and subsequent need for allogeneic blood transfusions. We hypothesized that aggressive, comprehensive blood conservation strategies may limit the need for transfusions and, subsequently, improve postoperative outcomes. Methods: Over a five-year period, 189 patients underwent proximal aortic surgery at our institution. Fifty-one patients underwent surgery using a comprehensive blood conservation strategy (BCS), including preoperative hemoglobin optimization, antifibrinolytic therapy, intraoperative acute normovolemic hemodilution, cell salvage and meticulous surgical technique. The remaining 138 patients underwent surgery using conventional techniques (CONV). Results: Patients in the BCS group required fewer transfusions during their hospital stay compared to the conventional group (56.9% vs. 72.5%, p=0.041). When examining elective cases, this trend widens, with 40.0% of BCS patients requiring any transfusions compared to 72.9% patients in the conventional group (p=0.001). Red cell (47.1% vs. 62.3%, p=0.06), plasma (43.1% vs. 61.6%, p=0.02) and platelets (27.5% vs. 47.8%, p=0.01) were also less frequently required in the BCS group than the conventional group, respectively. When a transfusion was required, patients in the BCS group received significantly fewer units of red blood cells (2.8 ± 7.0 units) than the conventional group (5.81 ± 9.5 units; p=0.039). Mortality was similar in both groups (BCS 7.8%, conventional 10.9%, p=0.54); however, there was significantly less morbidity in the BCS group, using a composite of any of 10 major postoperative complications (23.5% vs. 39.1%; p=0.046). Median intensive care unit (ICU) and hospital lengths of stay were 2 and 7 days in the BCS group and 2 and 8 days in the CONV group (p=0.15), respectively. Conclusions: The aggressive use of a comprehensive blood conservation strategy in ascending and aortic arch surgery can significantly reduce the need for blood transfusions and is associated with less postoperative morbidity. Further evaluation with a randomized, controlled trial is warranted.